The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0300060517695008
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal screening for fetal common sex chromosome aneuploidies from maternal blood

Abstract: ObjectiveTo explore the feasibility of high-throughput massively parallel genomic DNA sequencing technology for the noninvasive prenatal detection of fetal sex chromosome aneuploidies (SCAs).MethodsThe study enrolled pregnant women who were prepared to undergo noninvasive prenatal testing (NIPT) in the second trimester. Cell-free fetal DNA (cffDNA) was extracted from the mother’s peripheral venous blood and a high-throughput sequencing procedure was undertaken. Patients identified as having pregnancies associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
88
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 35 publications
14
88
2
Order By: Relevance
“…In several large prospective studies, the specificity of NIPS for SCAs detection was consistently low, leading to relatively higher false‐positive rates . Previously, we demonstrated that the overall predictive positive rate of NIPS for SCAs was 54.54% . In 2016, the international guidelines issued by the American College of Obstetricians and Gynaecologists (ACOG) claimed that the false‐positive rate of SCAs by NIPS was approximately 1% …”
Section: Introductionmentioning
confidence: 95%
“…In several large prospective studies, the specificity of NIPS for SCAs detection was consistently low, leading to relatively higher false‐positive rates . Previously, we demonstrated that the overall predictive positive rate of NIPS for SCAs was 54.54% . In 2016, the international guidelines issued by the American College of Obstetricians and Gynaecologists (ACOG) claimed that the false‐positive rate of SCAs by NIPS was approximately 1% …”
Section: Introductionmentioning
confidence: 95%
“…Noninvasive prenatal testing has been recommended as a first‐tier or second‐tier screening test for fetal common trisomies, with lower false‐positive rates and higher positive predictive values than serum biochemical screening . Noninvasive prenatal testing can also enable the detection of other aneuploidies, including sex chromosome aneuploidies (SCA) and structural chromosomal abnormalities . However, most of the published data have mainly focused on 3 common aneuploidies, SCA, and subchromosomal deletions/duplications.…”
Section: Introductionmentioning
confidence: 99%
“…Gonosomal aberrations are theoretically exposed during NIPT in a similar way as any other aneuploidy. Nevertheless, the specificity is reported to be much lower in comparison with traditional screening of chromosomes 13, 18, and 21, especially for monosomy X . Ethical issues on reporting these sometimes nonsevere abnormalities aside, the incorporation of FF in statistical outcome—which is generally not done with, eg, the popular z ‐score approach—does improve performance .…”
Section: Discussionmentioning
confidence: 99%